2016
DOI: 10.5958/2349-4433.2016.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic Supplementation on Growth Performance of Pre-Ruminant Buffalo Calves

Abstract: To study the effect of Probiotic (Saccharomyces cervisiae) supplementation in pre-ruminant (0-3 months age) buffalo calves, twenty buffalo calves were divided into two groups of ten calves each according to their body weight. One group was the control while the other group was supplemented with bacteria Saccharomyces cervisiae-containing Probiotic @ 15g/calf/d in milk for a period of two months under field condition. Fortnightly growth rate of calves revealed that the effect of Saccharomyces cervisiae was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Probiotics came up as a good adjuvant to promote the overall health in general and stabilization of gastrointestinal microbiota in particular as an alternative to antibiotics and becoming widely popular in this regards. It is well known that feeding calves with probiotics, especially lactic acid bacteria (Sharma et al 2016), improves gut health of neonate with a subsequent increase in digestion efficiency and it lead to better growth performance (Frizzo et al 2010). Scanty information is available regarding L. acidophilus action on blood biochemical profile, antioxidant modulation and plasma immunoglobulin level, particularly in neonatal Murrah buffalo calves.…”
mentioning
confidence: 99%
“…Probiotics came up as a good adjuvant to promote the overall health in general and stabilization of gastrointestinal microbiota in particular as an alternative to antibiotics and becoming widely popular in this regards. It is well known that feeding calves with probiotics, especially lactic acid bacteria (Sharma et al 2016), improves gut health of neonate with a subsequent increase in digestion efficiency and it lead to better growth performance (Frizzo et al 2010). Scanty information is available regarding L. acidophilus action on blood biochemical profile, antioxidant modulation and plasma immunoglobulin level, particularly in neonatal Murrah buffalo calves.…”
mentioning
confidence: 99%
“…Similarly, Sharma et al, (2016) concluded that feeding probiotic (Saccharomyces cerevisiae) @ 15g/calf/day in milk for a period of two months resulted in improved (P<0.05) growth rate of buffalo calves under field condition. Feeding of direct fed microbes (Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus plantarum, Bacillus subtilis and Aspergillus oryzae) and exogenous fibrolytic enzymes (pectinase, lipase, protease, amylase and cellulase) @ 10 g per animal to Brown Swiss x Eastern Anatolian RedF1 calves resulted higher (P<0.05) weights and growth rate than control group (Kocyigitet al, 2016).…”
Section: Body Weight and Growth Ratementioning
confidence: 97%
“…However, the reduction in TLC values following treatment might be due to control of infection in the patients during our study period. The combination of potent antibacterial agent and synbiotic might have blocked the rapid multiplication of pathogenic bacteria in the present therapeutic trial (Sharma et al, 2016).…”
Section: Haemoglobin (G/dl)mentioning
confidence: 98%